Understanding the interactions between Borrelia duttonii and the tick Ornithodoros moubata as well as the mammalian host at the in vitro and in vivo level - Bayer, Maximilian (Jihočeská univerzita, 2020)
The aim of this Bachelor thesis was to study the interactions between the spirochete B. duttonii, which is a causative agent for relapsing fever in Africa, and its vector, the soft tick O. moubata. Several experiments were conducted including passaging, membrane feeding and keeping infected ticks at different temperatures. Microscopy experiments were carried out to visualize the presence of B. duttonii in mammalian blood cells and in the salivary glands of the O. moubata tick.
Understanding the interactions between Borrelia duttonii and the tick Ornithodoros moubata as well as the mammalian host at the in vitro and in vivo level
Keywords: Molecular ecology; vectors and parasites; relapsing fever; Borrelia; soft tick; Molecular ecology; vectors and parasites; relapsing fever; Borrelia; soft tick